Łacińskie paremie na gmachach sądów w Białymstoku przejawem europejskiej tradycji prawnej - Niczyporuk, Aleksandra (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Łacińskie maksymy znajdujące się na budynkach sądów w Białymstoku przy ul. Mickiewicza mają ponadczasowe znaczenie w europejskiej tradycji prawnej. Ich obecność potwierdza żywotność prawa rzymskiego w wymiarze sprawiedliwości. W tekście przedstawiono kilka maksym, jednak tylko dwie z nich pochodzą ze źródeł ius Romanum. Trzecia ma ponadczasowy charakter i jest związana z chrześcijańskimi fundamentami cywilizacji europejskiej. Umieszczone maksymy pokazują drogę od pozwu aż po sprawiedliwy wyrok. Sprawiedliwość jest istotna podczas całej procedury rozpatrywania roszczenia. Trzeba podkreślić, że na przestrzeni stuleci maksymy łacińskie nie straciły znaczenia dla współczesnej polskiej i europejskiej praktyki prawniczej.

Latin Maxims on the Judicial Buildings in Białystok Latin maxims located on the buildings of the courts in Białystok, located in Mickiewicza street, have a timeless meaning in European legal tradition. Their presence is a sign that the modern Polish jurisdiction implements the idea of Roman law. However, only two of them originate in ius romanum sources. The third one also has a timeless nature and is connected with the Christian foundation of European civilization. The location of maxims, not exactly intended by their inventors, shows the path that must be followed in the court body. Everything starts with the statement of claim and, then, justice must be done in all its dimensions, until the fair sentence. During the many centuries of change and historical development, the latin maxims did not lose their validity and significance for modern Polish and European legal practice.
Keywords: prawo rzymskie; paremie łacińskie; tradycja prawna; ustawa XII tablic; rzymska procedura cywilna; roman law; latin maxims; legal tradition; twelve tables; Roman civil proceedings